Hydatid disease of liver and disseminated hydatidosis: anatomical, microbiological and radiological perspective - Hassan, Ashfaq Ul; ., Obaid; Shafi, Sajid; Hassan, Muneeb Ul; Rather, Aijaz (International Journal of Research in Medical Sciences, 2017)
The article underlies the geographic locations of the disease as the disease is not uniformly distributed and is common in certain parts of the world and rare in other parts. The article tries to summarize the microbiological aspects along with the anatomical and surgical perspectives for in depth knowledge and reasons for spread of disease. The photographs indicate the radiological spectrum of the disease in line with the text.